From System Collapse to Chavista Hegemony: The Party Question in Bolivarian Venezuela. (January 2017) - Hetland, Gabriel
During the 14 years Hugo Chávez was in office, Venezuela's party system experienced a 180-degree shift. When Chávez was elected in 1998, Venezuela's party system had collapsed because of a two-decade-long economic-cum-political crisis. His initial appeal was built, in large part, on his antiparty message, a stance that continued through the first half of his time in office. A series of factors, principally the need for a more cohesive organization to combat an intransigent opposition, led to the creation of the Partido Socialista Unido de Venezuela (United Socialist Party of Venezuela—PSUV) in 2007. The PSUV quickly became Venezuela's largest party and the linchpin of a new hegemonic system. The contradictions of that system are manifested in the split between the PSUV's right and left wings, and the hegemony of Chavismo is now in doubt. Durante los 14 años de la presidencia de Hugo Chávez, el sistema de partidos de Venezuela sufrió un giro de 180°. Cuando Chávez fue elegido en 1998, el sistema ya había colapsado debido a la larga crisis económica y política que ya llevaba dos décadas. Su llamamiento inicial se fundamentó, en gran parte, en un mensaje antipartido, una postura que continuó durante la primera mitad de su mandato. Una serie de factores—principalmente, la necesidad de una organización más cohesiva para combatir a la oposición intransigente — llevó a la creación del Partido Socialista Unido de Venezuela (PSUV) en 2007. El PSUV rápidamente se convirtió en el partido más grande de Venezuela y en la pieza esencial de un nuevo sistema hegemónico. Las contradicciones del sistema se manifiestan en la brecha entre el ala izquierdista y el ala derechista del PSUV y la hegemonía del chavismo ahora está en entredicho.